Scattering of Photons by Many-Electron Systems - Hopersky, Alexey N.; Yavna, Victor A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book deals with quantum physical calculations of anomalous scattering of photons by bound electrons. The main attention is paid to studies of the process of photon scattering in the energy range of deep levels of such many-electron systems as atoms, atomic ions and simple molecules. The book is written for scientists and graduate students, working in the field of atomic and molecular spectroscopy, physics of plasmas, lasers, solid state, ionizing radiation and astrophysics. It can also be used as additional textbook for a special topic of quantum mechanics.
Research Results of the Process of the Anomalous Elastic X-Ray Photon Scattering by a Many-Electron System -- Many-Particle Effects at Anomalous Elastic X-Ray Photon Scattering by an Atom and an Atomic Ion -- Effect of the Deep Vacancy Auger-Decay When Anomalous Elastic X-Ray Photon Scattering by an Atom -- Many-Particle and Orientation Effects When Anomalous Elastic X-Ray Photon Scattering by a Linear Molecule.
Keywords: Physics; Quantum theory; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Quantum Physics